2011 IEEE Power and Energy Society General Meeting 2011
DOI: 10.1109/pes.2011.6039593
|View full text |Cite
|
Sign up to set email alerts
|

A community based approach for sustainable off-grid PV systems in developing countries

Abstract: The energy requirements of developing countries underpin progress towards achieving the Millennium Development Goals (MDGs). Rural electrification is acknowledged as key to providing a source of reliable, affordable and sustainable energy. Many planners and decision makers agree that the off-grid PV system has the potential to become a valued and straightforward source of electricity for remote rural communities. However, there are several challenges that need to be addressed to realize the potential of PV as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 5 publications
0
19
0
Order By: Relevance
“…The economic sustainability of electrification solutions requires ensuring the funding or affordability of the systems (i.e., the initial investments and the Operation and Maintenance (O&M) over its lifetime) [24,26,29,35,38,[44][45][46][47]. In the energy sector, other important indicators for the economic sustainability of electrification solutions are the cost-effectiveness [25,26,46,48] and the reliability of supply (see, e.g., [25][26][27]34,49,50]).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 2 more Smart Citations
“…The economic sustainability of electrification solutions requires ensuring the funding or affordability of the systems (i.e., the initial investments and the Operation and Maintenance (O&M) over its lifetime) [24,26,29,35,38,[44][45][46][47]. In the energy sector, other important indicators for the economic sustainability of electrification solutions are the cost-effectiveness [25,26,46,48] and the reliability of supply (see, e.g., [25][26][27]34,49,50]).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…For an energy system to be sustainable, it needs to be socially accepted, which implies the active participation and engagement of the community aimed at enhancing the accountability of the project [40,47,50,56,60,189,190]. Off-grid PV systems can be a great opportunity to assure social acceptance; Burton and Hubacek [191] found that, compared to large-scale solutions, small-scale energy approaches may have a higher social acceptance.…”
Section: Social Acceptancementioning
confidence: 99%
See 1 more Smart Citation
“…In that context, Gollwitzer [19] highlights the importance of adopting and enforcing norms and regulations. Authors further agree on the relevance of the openness to people's participation [20][21][22] and of decentralization [23,24], which favors the adaptability to local needs [14,17,21,25].…”
Section: Cultural Justicementioning
confidence: 98%
“…Socio-cultural sustainability also requires social acceptance (which implies a participatory and inclusive approach in which the local community is engaged to increase their accountability for a technology; [37,54,55]); as well as accuracy (which comprises the selection of the technology appropriate to the local consumer demands; [23,42]). …”
Section: Theoretical Frameworkmentioning
confidence: 99%